Hubungan Terpaan Iklan Imagine Your Korea Dengan Minat Berkunjung Masyarakat Denpasar - Gunawan Putri, Stephanie; Purnawan, Ni Luh Ramaswati; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2019)
ABSTRACT The development of Korean Wave that spread rapidly throughout the world made South Korea utilize this phenomenon to develop their tourism sector. Indonesia as the largest Korean Wave market in Southeast Asia became opportunity for South Korea to promote their tourism. The promotion is uploaded to YouTube to reach audiences. This study is aimed to determine the relationship between exposures of 8 Faces of Korea, 8 Types of Trip tourism advertisement with interest of Denpasar citizen. The sampling method in this research is non-probability purposive-sampling. Primary data was collected through questionnaires distributed to respondents aged 19 to 39 who had seen the advertisements at least once. This study shows that advertisement exposure has a significant and quite strong relationship with the interest of visiting. Relationship between the two variables is unidirectional, which means the more exposure happens to audience, the higher interest to visit. Keywords: Imagine Your Korea, Intention to visit, Media Exposure, Tourism.